2020
DOI: 10.3389/fpsyg.2020.00303
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Variability, Sighing, Anxiety, and Breathing Symptoms in Low- and High-Anxious Music Students Before and After Performing

Abstract: Music performance anxiety (MPA) is a major problem for music students. It is largely unknown whether music students who experience high or low anxiety differ in their respiratory responses to performance situations and whether these co-vary with selfreported anxiety, tension, and breathing symptoms. Affective processes influence dynamic respiratory regulation in ways that are reflected in measures of respiratory variability and sighing. This study had two goals. First, we determined how measures of respiratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 69 publications
(102 reference statements)
0
15
0
Order By: Relevance
“…A first challenge would be having a similar number of male and female participants to avoid a gender bias. Previous studies on the same population [7,21] showed that, on average, 60 to 67% of the sample were female. Having a well-balanced gender ratio is important considering gender differences in the prevalence of anxiety disorders [87,88] and especially of MPA [2], and in the psychophysiological response to stressors [89].…”
Section: Possible Challengesmentioning
confidence: 86%
See 2 more Smart Citations
“…A first challenge would be having a similar number of male and female participants to avoid a gender bias. Previous studies on the same population [7,21] showed that, on average, 60 to 67% of the sample were female. Having a well-balanced gender ratio is important considering gender differences in the prevalence of anxiety disorders [87,88] and especially of MPA [2], and in the psychophysiological response to stressors [89].…”
Section: Possible Challengesmentioning
confidence: 86%
“…Regarding physiological measures, skin conductance, heart rate (HR), urinary adrenaline and noradrenaline did not show significant differences as a function of musicians' general MPA level [3,6,8]. In contrast, analyses of the respiratory responses showed that the general MPA level significantly moderated changes from a private to a public performance in partial pressure of end-tidal carbon dioxide (P et CO 2 ), total respiratory variability (quantified by the coefficient of variation) and sigh rate [7,8]. Salivary cortisol (sC), salivary dehydroepiandrosterone (sDHEA), and salivary alpha-amylase (sAA) have yet to be considered in relation to potential MPA-associated differences in the context of music performance.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Research on music performance anxiety (MPA) has been conducted for several decades and is still ongoing ( Fishbein et al, 1988 ; Steptoe, 2001 ; Kenny and Osborne, 2006 ; Kenny, 2011 ; Topoğlu, 2014 ; Guyon et al, 2020b ). MPA is a globally negative and debilitating psychological phenomenon in musicians regardless of age, gender, experience, practicing time, and music genre ( Brugués, 2011a , b ; Studer et al, 2011 ; Barbar et al, 2014 ; Nusseck et al, 2015 ; Bannai et al, 2016 ; Sousa et al, 2016 ; van Fenema et al, 2017 ; Burin et al, 2019 ; Guyon et al, 2020a ). MPA had been identified in music students and shown statistically significant differences in various psychological constructs, including optimism, self-efficacy, achievement motivation, and sensitivity to reward and punishment ( Alzugaray et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Acutely higher respiratory variability in reaction to anxious or otherwise stressful stimuli is a biologically adequate response and will resolve after some time (e.g. Guyon et al., 2020 ). In contrast, longer lasting high respiration pattern variability (RPV) instead of regular deep abdominal breathing is considered maladaptive and seems related to psychological problems ( Asnaashari et al., 2012 ; Vlemincx et al., 2013 ).…”
Section: Introductionmentioning
confidence: 99%